Correlation between neurologic status and spinal injury at the Cervicothoracic Junction - Dhakal, Gaurav Raj; Sadiqi, Said; Shah, Gyanendra; Shrestha, Sushil; Paudel, Santosh; Kawaguchi, Yoshiharu; Riew, K.Daniel (Journal of Nepal Health Research Council, 2022)
Background: With limited studies on spinal injuries occurring at the cervicothoracic junction, there is currently a knowledge gap regarding the correlation between morphology of injury and neurology and whether surgery provides a favorable neurological outcome. The primary objective was to determine whether the neurological deficit correlated with the severity of injury at this region of the spine.Methods: All patients with injuries at the cervicothoracic junction from December 2015 to December 2020 in a government trauma hospital were included. Patient demographics, characteristics of the injury, neurological score, imaging findings, surgery details and neurological outcomes were analyzed. All patients had a minimum follow up of 2 years.Results: Of the total 30 patients, 23 were male and 7 female with mean age 42.4 years. 90% had fall injuries with 76.7% sustaining AO type C injury and 10% with AO B2 injury.73.4% had injury at C6-C7 level followed by 13.3% , C7-T1. Only 16.7% patients presented with intact neurology. Plain x-rays failed to detect cervicothoracic junction, injuries in 63.3% patients. Posterior stabilization was performed in 56.7%. Neurological improvement was observed in 9 patients.Conclusions: Though cervicothoracic junction injuries are uncommon, they are highly unstable injuries and difficult to diagnose by plain x-rays. These injuries also result in profound neurological deficit. Surgical stabilization of these injuries should be considered for a favorable neurological and functional outcome. Keywords: Cervico-thoracic junction; injuries; morphology; neurology; spine.